The Effectof Corporate Social Responsibility Disclosure on Financial Performance: Comparative Study of Textile Companies Listed on Indonesia And Taiwan Stock Exchanges - Christine Dian Pertiwi; Anik Irawati; Jiin Feng Chen (Prosiding International conference on Information Technology and Business (ICITB), 2020)
The purpose of this study was to analyze the effect of CSR Disclosure on financial performance and the comparison between Indonesia and Taiwan Textile Companies listed on the Indonesia Stock Exchange and Taiwan Stock Exchange. The sample selection in this study used five textile companies in Taiwan and five textile companies in Indonesia in 2015-2017. The results of this study indicated that there was no effect of CSR disclosure on Assets Turnover (ATO) ratio and Return on Assets (ROA) ratio.Keywords  : CSR Disclosure, Financial Performance, Assets Turnover, Return on Assets